Improving Mixed-Reality Prototyping through a Classification and Characterisation of Fidelity. (May 2022) - Cox, C.; Hicks, B.; Gopsill, J.
Abstract: Prototyping is a vital activity in product development. For reasons of time, cost and level of definition, low fidelity representations of products are used to advance understanding and progress design. With the advent of Mixed Reality prototyping, the ways in which abstractions of different fidelities can be created have multiplied, but there is no guidance on how best to specify this abstraction. In this paper, a taxonomy of the dimensions of product fidelity is proposed so that both designers and researchers can better understand how fidelity can be managed to maximise prototype value.